Transfusional Malaria and Associated Factors at the National Blood Transfusion Center of Niamey-Niger - Aminata Iro; Moustapha Mahamane Lamine; Ramatoulaye Hamidou Lazoumar; Ibrahim Alkassoum; Daou Maman; Harouna Amadou Mahaman Laouali; Mahamadou Doutchi; Seydou Maiguizo; Ibrahim Maman Laminou (Journal of Tropical Medicine)
Summary. Problem. Transfusional malaria is an accidental transmission of Plasmodium via a blood transfusion. Its magnitude is underestimated and very little data on the assessment of this risk are available in Niger. Objective. This study aimed to determine the prevalence of plasmodial infection of blood bags at the National Blood Transfusion Center of Niamey (NBTC). Methodology. A cross-sectional study to diagnose Plasmodium infection by microscopy and Rapid Diagnostic Test (RDT) was carried out during the rainy season (September to November 2015). Blood grouping was performed by the BETH-VINCENT technique. Results. One thousand three hundred and fifty-seven (1357) blood bags were collected. One hundred and fifty-seven (11.6%) of the donors were infected with Plasmodium by microscopy and 2.4% (9/369) by rapid diagnostic test. All infections were with P. falciparum (100%). The mean parasite density was 197 parasites/μL (SD=281; [80: 2000]). There were no significant differences in infection prevalence between the ABO blood groups (p=0.3) or the rhesus positivity (p=08). There is also no significant difference in temporal (p=0.1) and spatial (p=0.6) distribution. Conclusion. The transmission of transfusional malaria during the rainy season is a fact in Niger. Such risks were independent of the ABO blood type and positivity for the rhesus antigen. Pretransfusion diagnosis or posttransfusion therapy should be instituted to prevent it.